The Influence of Audio Visual Media With Animated Films on Children's Speaking Skills in Kindergarten - Yuli Ernita; Farida Mayar (AL-ISHLAH: Jurnal Pendidikan, 2023)
The ability to speak provides an overview of the child's ability to compose various words that have been mastered into a structured series of conversations. The purpose of this study was to determine the influence of the application of audiovisual media with animated films on the speaking ability of children in kindergarten. The method used in this study is research with an experimental approach: One-group pre-test-post and test design. The results obtained are that the significance is 0.000 0.05, then Ha is accepted, and Ho is rejected, meaning that the hypothesis states that there is a difference in children's speaking abilities after using Audiovisual Media with Animation Film. The provision that the results show an average difference of -3.956a  and a sig (2-tailed) value of 0.000. This means that the sig value 0.05 means that Ha is accepted and Ho is rejected. Thus it can be concluded that audio-visual media with animated films can improve children's speaking skills in kindergarten.